2007
DOI: 10.1097/01.jcn.0000287027.49628.a7
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Symptom Diary for Self-monitoring in Heart Failure Clinic Patients

Abstract: Diary users showed evidence of improved clinical and hospital outcomes. Further investigation is needed to clarify the characteristics of a diary user and the effect of diary use on self-management and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“…Although the most prevalent signs and symptoms were consistent with findings reported in the literature, [13][14][15][16][17][18][19] patients in our study reported some rarely discussed signs and symptoms, such as change in urine output; cool, pale, or mottled skin; and irregular pulse. Our findings may be more comprehensive as a result of our use of the checklist format.…”
Section: Discussionsupporting
confidence: 81%
“…Although the most prevalent signs and symptoms were consistent with findings reported in the literature, [13][14][15][16][17][18][19] patients in our study reported some rarely discussed signs and symptoms, such as change in urine output; cool, pale, or mottled skin; and irregular pulse. Our findings may be more comprehensive as a result of our use of the checklist format.…”
Section: Discussionsupporting
confidence: 81%
“…Although the study was a retrospective analysis, majority of those enrolled used the diary and had better outcomes than did the nondiary users. 30 Thus, it seems that patients are willing and able to track symptoms but may need more intensive self-management support to take action based on the data. 31 Self-monitoring is a consistently effective strategy to change health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study of Eastwood et al in 2007, weight and symptom self-monitoring diary users indicated improvement in HF clinical and hospital outcomes [34].…”
Section: Patient With Hf Experience Weight Gain and Other Symptoms Ofmentioning
confidence: 99%